PENGARUH TINGKAT PENDIDIKAN, PEMAHAMAN AKUNTANSI, SOSIALISASI SAK EMKM, DAN KESIAPAN PELAKU UMKM TERHADAP PENERAPAN SAK EMKM PADA USAHA MIKRO KECIL DAN MENENGAH (UMKM) PENGOLAHAN MAKANAN RINGAN DI KECAMATAN BOYOLALI KABUPATEN BOYOLALI - Ani Muslihah Rositasari; Alean Kistiani Hegy Suryana; Yunita Niqrisah Dwi Pratiwi (Universitas Boyolali, 2022)
This study aims to determine the effect of education level, accounting understanding, socialization of SAK EMKM, and readiness of UMKM actors on the application of SAK EMKM to UMKMs in Snack Processing in Boyolali District, Boyolali Regency. The population in this study is Snack Processing UMKMs that have been registered and have an IUMK with a sample of 40 respondents. Data obtained by distributing questionnaires, analyzed using classical assumption test, research instrument test, and hypothesis testing. The results of this study are the educational level significance value of 0.780 > 0.05 which means that H1 is rejected so that it is said that the education level variable has no significant effect on the application of SAK EMKM to UMKMs. The significance value of accounting understanding is 0.012 <0.05, which means that H2 is accepted so that it is said that the accounting understanding variable has a positive influence on the application of SAK EMKM. The significance value of SAK EMKM socialization is 0.001 <0.05, which means that H3 is accepted so that it is said that the socialization variable has a positive influence on the implementation of SAK EMKM. The significance value of the readiness of UMKM actors is 0.164 > 0.05, which means that H4 is rejected, so it is said that the UMKMs actor readiness variable does not have a significant influence on the implementation of SAK EMKM.